The Role of Public Relations of the Sukabumi City DPRD Secretariat in Delivering Public Information - Fajri, Raisya Halimatunnisa; Nugroho, David Rizar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Public relations (PR) plays a strategic role in bridging communication between government institutions and the public to achieve transparency in public information. The Public Relations Division of the Secretariat of the Regional House of Representatives (DPRD) of Sukabumi City is required to deliver information effectively, transparently, and accountably. This study aims to identify the role of the PR Division in providing public information. A descriptive qualitative method was employed, with the research conducted at the DPRD Office of Sukabumi City. Data collection techniques included observation, interviews, and documentation. Informants in this study consisted of the Head of Public Relations, PR staff, and representatives of DPRD members.The object of this research is the PR Division of the DPRD Secretariat of Sukabumi City, particularly its role in delivering public information. Data analysis followed the Miles and Huberman model, encompassing data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that the duties of the PR Division go beyond documentation and media coverage; they also serve as communicator, relationship builder, management support, and image maker. Social media and collaboration with mass media are utilized as the main communication channels for disseminating public information. The main obstacles include limited human resources and inadequate supporting facilities. Overall, the PR Division has performed its role fairly well, although improvements are still needed through capacity building and technical support.